Impact of semaglutide on osteoarthritis risk in patients with obesity: A retrospective cohort study - Onur Baser; Lauren Isenman; Sefika Baser; Gabriela Samayoa (Wiley, 2024)
Abstract Background Osteoarthritis (OA) is a prevalent degenerative joint disorder. While the effect of obesity on OA is well documented, less is known about the effect of semaglutide on OA. Objective To determine the impact of semaglutide on the risk of OA in patients with obesity in the United States. Methods A retrospective cohort study was conducted utilizing Kythera Medicare closed claims data from November 1, 2020 to October 31, 2023. Continuously enrolled patients with obesity diagnoses during the baseline period (November 1, 2020- October 31, 2021) were identified and grouped based on whether they had or had not used semaglutide during the identification period (November 1, 2021- October 31, 2022) and followed if they had OA during the follow‐up period. Multivariate analysis was utilized to adjust for demographic variables and comorbidities. Results We identified 1360 patients taking semaglutide and 39,891 patients not taking semaglutide. The most common comorbidities were chronic obstructive pulmonary disease, depression, and anxiety. After controlling for demographic and clinical factors, the semaglutide cohort had a significantly lower risk of OA than the non‐semaglutide cohort (HR, 0.84; p = 0.0069). Conclusions This study suggests that semaglutide may have the potential to help in preventing OA.